Pelatihan Pembuatan Powerpoint Sebagai Media Pembelajaran Pada Guru Raudhatul Athfal Usman Baharun Ba’alawi Bengkel Lombok Barat. - Hakim, Samsul; Hadi, Alfan (Jurnal Pengabdian Kepada Masyarakat Al-Amin, 2023)
This Community Service activity teaches educators how to make PowerPoint-based learning media to be used in the learning process at school. Action research, or called action research, is the method used and has four steps: preparing, implementing, observing, and evaluating or reflecting. As many as 11 RA Usman Baharun Ba'alawi teachers became partners in the PKM activities, which were carried out for two days. According to the results, as many as 80% of the participating teachers could complete PowerPoint-based learning media thoroughly. So, this activity has the potential to have a positive impact because the participants (teachers) have improved their abilities in operating laptops or computers. They also can make learning using PowerPoint-based media, and the learning media created by the teacher can be applied directly to the learning process at school.